Pulmonary dysfunction-an overt leprosy sequel: study done in a rehabilitation centre - Achuthan, Anitha; BalaKrishnan, Priyadharshini (International Journal of Research in Medical Sciences, 2017)
Background:In India, a total of 1.35 Lakh new cases were detected during the year 2012-13, which gives annual new case detection rate (ANCDR) of 10.78 per 100,000 populations. The proportion of multibacillary cases is 49.92 %. New cases continue to occur in almost all the endemic countries indicating that high burden pocket can exist against a low burden back ground. Leprosy is a mono neuritis multiplex complex of immunological origin that results in autonomic, sensory and motor neuropathy. This impairs pulmonary chemo sensitivity because of the block of vagus and sympathetic plexus in leprosy patients. Even after the treatment, a predisposition to nerve damage continues, as the clearance of bacterial antigens is extremely slow. The study aims at assessing the respiratory function in treated leprosy patients. Methods: 23 treated leprosy patients were selected after written and informed consent according to the inclusion and exclusion criteria. After obtaining the clearance from Institutional ethical committee, pulmonary function test was performed and the lung parameters were measured using computerized spirometry. Results: The statistical analysis revealed significant decrease in FVC%, FEV1%, FEV1/FVC% in lepromatous patients compared with tuberculoid patients. The restrictive pattern predominates in both lepromatous and tuberculoid patients. Conclusions: The study concluded that there is a definite impairment of lung functions in the patients treated for leprosy, causing spontaneous respiratory arrest and unexplained sudden deaths. Since the results have statistical significance, the study warrants early detection of respiratory abnormalities in leprosy patients who don’t have any clinically detectable symptoms.